Phylogenetic diversity of culturable bacterial endophytes associated with Avicennia marina from coastal mangroves of the Eastern Province, Saudi Arabia - ASMA A. ALANAZI; INÈS HAMMAMI; AISHA ALSHAMMARI; HANAN ALMAHASHEER (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Alanazi AA, Hammami I, Alshammari A, Almahasheer H. 2026. Phylogenetic diversity of culturable bacterial endophytes associated with Avicennia marina from coastal mangroves of the Eastern Province, Saudi Arabia. Biodiversitas 27 (2): d270201. https://doi.org/10.13057/biodiv/d270201. Mangrove ecosystems host diverse endophytic bacterial communities that contribute to plant survival under saline and tidally fluctuating environments. This study investigates the phylogenetic diversity and in vitro functional traits of culturable bacterial endophytes associated with Avicennia marina collected from coastal mangroves of the Eastern Province, Saudi Arabia. A total of sixteen bacterial isolates were recovered from leaf tissues and identified based on 16S rRNA gene sequencing, revealing dominance of the genus Bacillus (B. safensis, B. subtilis, B. amyloliquefaciens, B. megaterium, and B. inaquosorum), along with Brevibacterium halotolerans, expanding current knowledge of region- and host-associated mangrove endophytes functional screening demonstrated variable hydrolytic enzyme activities, including protease, amylase, cellulase, and chitinase production. Qualitative dye-decolorization assays showed that several isolates were capable of transforming lignin-mimicking dyes under laboratory conditions. In vitro antibacterial activity against selected human pathogens was observed in a subset of isolates, with minimum inhibitory concentrations ranging from 0.312 to 5 mg/mL. Scanning electron microscopy revealed morphological alterations in treated bacterial cells, supporting the inhibitory effects observed in the antimicrobial assay. Overall, this study provides baseline data on the culturable endophytic bacterial diversity associated with A. marina in the Arabian Gulf region and highlights preliminary functional traits that warrant further genomic and in planta validation.